If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -3y) * 27x = 0 Reorder the terms for easier multiplication: 27x(5x + -3y) = 0 (5x * 27x + -3y * 27x) = 0 Reorder the terms: (-81xy + 135x2) = 0 (-81xy + 135x2) = 0 Solving -81xy + 135x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '27x'. 27x(-3y + 5x) = 0 Ignore the factor 27.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-3y + 5x)' equal to zero and attempt to solve: Simplifying -3y + 5x = 0 Reorder the terms: 5x + -3y = 0 Solving 5x + -3y = 0 Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 5x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 5x + 0 = 0 + 3y 5x = 0 + 3y Remove the zero: 5x = 3y Divide each side by '5'. x = 0.6y Simplifying x = 0.6ySolution
x = {0, 0.6y}
| log(3)+log(7)= | | 12-10x=86-24x | | 3w-6=4w-2 | | x=59+2500 | | 7-2z=-9 | | a=.5+28 | | 5(2Y-4)=2(5y-10) | | 3(x+4)+5(x+2)=4(x-1)+2 | | 2g+3(-7+3g)=1-g | | 25-3(x-4)=58 | | 6(x+12)-15=61 | | 2u+10=17 | | 2(x-7)-12=6 | | 7+2(x+5)=49 | | 3(x+4)+7=61 | | 3+9q=5+8q | | -3(x-5)=27 | | -4(x+6)=96 | | 2(x-14)=66 | | 5(-3)-15=-4(-3)+12 | | 5(x+6)=120 | | 5(3)-15=-4(3)+12 | | 3(x+2)=24 | | 2(4p-2)=-24 | | (x+4)(x+2)=x-(1-x^2) | | 1/2(6-3)=5/2 | | -k^2+11k-15=3 | | 18.9=2.1 | | (2-b)(2+5)-11=24 | | 7-x-x=-1 | | 27b=59 | | 7x=8+6 |